PENINGKATAN MATERI BOLA VOLI MELALUI AUDIO VISUAL PADA PESERTA DIDIK KELAS IV SD NEGERI LIDAH KULON I SURABAYA - Agung Prasetyo, Surya; Wibowo, Sapto; Thohari, Anang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the results of learning certain passing movements in the volleyball innovation game through audiovisual media. The research method uses the Classroom Action Research (PTK) method. The research was conducted in two cycles consisting of two meetings. The subjects of this research were class IV students at SDN Lidah Kulon I Surabaya, totaling 32 students, consisting of 8 female students and 24 male students. The level of completion achieved using data analysis techniques. Before carrying out the first cycle measurements, the researcher first gave a pre-cycle test to find out the students' initial abilities. As a result, only 37.5% of students reached the learning completion threshold. After the Cycle I actions were implemented, learning outcomes increased for 32 students: 2 students were able to reach the threshold for completeness with a percentage of 6.25%, 15 students were able to reach the threshold for completeness with a percentage of 46.8%, and 12 students were able to reach the threshold for completeness with a percentage of 37.5%. There were 3 students who did not reach the limit for learning completeness due to insufficient information, with a percentage of 9.4%.In Cycle II, there were 9 students who were able to reach the limit of learning completeness with very good information, with a percentage of 28.1%. The learning completeness threshold is expected to be achieved with a percentage of 56.2%; however, there are still five students who have not reached the learning completeness threshold with a percentage of 15.6%.